Investigation of the performance of driver mutation identification methods using biological networks and enriched biological networks - Souza, Alfredo Guilherme da Silva; Simao, Adenilso (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2022: Anais do XXII Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2022.222457, 2022)
Several computational methods allow identifying genes related to cancer (driver mutation) through patient mutation data and biological networks. Usually, networks are not built focusing on biological activities associated with cancer because they are designed for general use. In this study, we investigate the performance of methods for identifying driver mutations using biological networks and enriched biological networks, applying a gene prioritization method to classify genes associated with cancer understudy in the biological network. The results indicated that employing the enrichment method helped identify different driver genes in all cases.